Strategies for Sustainable Mangrove Tourism Development in Bulu Cindea - Maghrifa, Nurul; Malik, Abdul; Yusuf, Muhammad; Musyawarah, Rahma (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2025)
This study explores the potential and challenges of developing mangrove tourism in Bulu Cindea South Sulawesi Province Indonesia within the framework of the blue economy The research assesses the feasibility of leveraging the region s natural beauty and strategic location to promote sustainable tourism while addressing existing weaknesses and threats Using a SWOT analysis the study identifies key strengths such as the area s scenic vistas accessibility and broad mangrove ecosystems alongside weaknesses including inadequate promotion limited professional expertise and insufficient community involvement Growth opportunities include economic development strategic location community support and social media marketing while threats involve facility damage competition pollution and declining tourist interest The research employs qualitative and quantitative methods to evaluate these factors offering strategic recommendations to enhance the management and promotion of mangrove tourism These recommendations include improving promotional strategies upgrading infrastructure developing professional skills involving local communities and implementing effective environmental protection measures The findings contribute to sustainable tourism by demonstrating how targeted interventions can address barriers to development and align with blue economy principles ensuring economic benefits and ecological preservation This study provides valuable insights for policymakers local stakeholders and tourism developers seeking to foster sustainable tourism practices in similar environmental contexts < em>< p>